Multicontrast photoacoustic in vivo imaging using near-infrared fluorescent proteins - Krumholz, Arie (Nature Publishing Group, 2014)
Non-invasive imaging of biological processes in vivo is invaluable in advancing biology. Photoacoustic tomography is a scalable imaging technique that provides higher resolution at greater depths in tissue than achievable by purely optical methods. Here we report the application of two spectrally distinct near-infrared fluorescent proteins, iRFP670 and iRFP720, engineered from bacterial phytochromes, as photoacoustic contrast agents. iRFPs provide tissue-specific contrast without the need for delivery of any additional substances. Compared to conventional GFP-like red-shifted fluorescent proteins, iRFP670 and iRFP720 demonstrate stronger photoacoustic signals at longer wavelengths, and can be spectrally resolved from each other and hemoglobin. We simultaneously visualized two differently labeled tumors, one with iRFP670 and the other with iRFP720, as well as blood vessels. We acquired images of a mouse as 2D sections of a whole animal, and as localized 3D volumetric images with high contrast and sub-millimeter resolution at depths up to 8 mm. Our results suggest iRFPs are genetically-encoded probes of choice for simultaneous photoacoustic imaging of several tissues or processes in vivo.